Immunoglobulin G4-related disease with pleural involvement in an 80-year-old female patient: A case report and literature review - Liying Zhang; Li Mo (Experimental Gerontology)
Background: Immunoglobulin G4-related disease (IgG4-RD), a rare immune-mediated disease affecting multiple organs, rarely involves the pleura. This study presents a case of pleural IgG4-RD and reviews the literature to elucidate the patient population, manifestations, and diagnostic and treatment characteristics of pleural IgG4-RD. This study aimed to expand the existing case database of pleural IgG4-RD and enhance the understanding and management of this rare disease. Methods: We report a case of IgG4-RD involving the pleura in an 80-year-old woman with a weight of 62 kg and a body mass index (BMI) of 23.2 kg/m2. Additionally, we reviewed pleural biopsy-confirmed IgG4-RD cases in the PubMed, Scopus, Web of Science, Embase, and Science Direct databases. Results: Forty-one patients with IgG4-RD confirmed by pleural biopsy were included. The median age was 69 years, with male predominance (31, 75.6 %). The most common manifestations were pleural effusion (37, 90.2 %) and dyspnea (26, 63.4 %). Elevated serum IgG4 levels were observed in 38 patients (92.7 %), with a median value of 398.2 mg/dL. Twenty-six patients met two histological criteria for IgG4-RD. Thirty-seven patients received glucocorticoid therapy, 34 of whom achieved clinical improvement. Conclusions: IgG4-RD with pleural involvement mainly manifests as pleural effusion and dyspnea, responding to glucocorticoid therapy. The possibility of this disease should be considered in patients with pleural effusion and enlargement of tissues or organs. Medical staff should attach importance to the application of the Comprehensive Geriatric Assessment (CGA) and the Geriatric Interdisciplinary Team (GIT) in the disease management of older patients.